NL

Chứng minh đẳng thức :

a) a(b - c) - a(b + d) = -(c + d).

b) (a + b)^2 = a^2 + 2a.b +b^2.

 

QA
30 tháng 1 2020 lúc 20:45

a) Biến đổi vế trái:

a( b -c) - a(b +d)

= ab -ac - ab + ad 

= -ac + ad

= -( c +d) = Vế phải

b)Biến đổi vế trái:

(a +b)2

= (a +b)(a +b)

= a2 + ab + ab + b2

= a2 + 2ab + b2 = Vế phải

Bình luận (0)
 Khách vãng lai đã xóa

Các câu hỏi tương tự
NB
Xem chi tiết
VK
Xem chi tiết
HL
Xem chi tiết
TT
Xem chi tiết
XX
Xem chi tiết
DT
Xem chi tiết
PC
Xem chi tiết
HH
Xem chi tiết
TA
Xem chi tiết